2008
DOI: 10.1017/s0007114508945165
|View full text |Cite
|
Sign up to set email alerts
|

Urinary felinine excretion in intact male cats is increased by dietary cystine

Abstract: Felinine is a branched-chain sulfur amino acid present in the urine of certain Felidae, including domestic cats. The objective of the present study was to determine if additional cystine and/or dietary N would increase felinine and N-acetylfelinine excretion by intact male cats fed a low-protein (LP) diet. Feeding five adult intact male cats an LP diet (18·8 % of metabolisable energy (ME) as protein) v. a high-protein diet (38·6 % of ME as protein) resulted in a trend (P¼ 0·08) for decreased urinary felinine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…However, impairment of renal function is normally seen in older cats (Burkholder, ), while the mean age of the cats used in present study was only 3.55 years. Also, as mentioned earlier, the observed Fel:Cr ratios here were comparable with ratios found in earlier studies on felinine excretion (Hendriks et al., ,b), which indicates that the results may be considered reliable.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, impairment of renal function is normally seen in older cats (Burkholder, ), while the mean age of the cats used in present study was only 3.55 years. Also, as mentioned earlier, the observed Fel:Cr ratios here were comparable with ratios found in earlier studies on felinine excretion (Hendriks et al., ,b), which indicates that the results may be considered reliable.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study indicate that cat breeds indeed differ in felinine excretion when expressed as a ratio with urinary creatinine. The Fel:Cr ratios in this study are comparable with those published in earlier papers on this subject (Hendriks et al., ,b) and may thus be considered reliable. Expression of urinary components relative to the urinary creatinine concentration is commonly employed to compensate for possible variations in renal output.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Cysteine is an important component of proteins for their secondary structure [39] and is a major constituent of hair [44]. Cysteine also functions as an essential thiol donor for hepatocellular glutathione synthesis [39] and as a precursor for felinine [45,46] and taurine [39]. …”
Section: Feline-specific Metabolic Featuresmentioning
confidence: 99%
“…127 Further studies have also shown the presence in Felis catus urine of 78, 79 and 80. 128,129 The site of felinine synthesis in vivo remains unknown; the biosynthesis appears to occur through a condensation of isopentylpyrophosphate and glutathione by an uncharacterized glutathione sulphur transferase. A recent study confirmed the presence of a felinine precursor 79.…”
Section: 76mentioning
confidence: 99%